Host-associated cues and their effects on the jumping behavior of Steinernema siamkayai - Puping Ta-oun; Toyoshi Yoshiga (Biological Control, 2025)
Entomopathogenic nematodes are insect parasites with infective juveniles (IJs) employing host-seeking behaviors from ambush to cruise foraging. In ambush-foraging species, IJs often exhibit jumping behavior for attachment to host insects. Steinernema siamkayai, an ambush forager, exhibits both standing and jumping behaviors. However, the factors that enhance this behavior in S. siamkayai and how these factors differ among ambush foragers remain poorly understood. We investigated the influence of insect-associated cues on the jumping behavior of the Thai strain of S. siamkayai compared with S. carpocapsae. In the absence of stimuli, both species jumped 5.5 ± 1.9 mm and 3.8 ± 0.7 mm, respectively, with no observable effect of stimuli on jump distance. However, insect odors and CO2 triggered directional jumping toward the source, while the proportion of jumps toward insect odors decreased when CO2 was removed for both species. A higher percentage of S. siamkayai responded to insect odors by jumping compared with S. carpocapsae. Notably, air movement insignificantly affected S. siamkayai jumping, unlike in S. carpocapsae. An increase in stable standing behavior was observed in S. siamkayai populations when the absence of host cues. Furthermore, when stimulated by insect odors and CO2, S. siamkayai jumped twice as quickly as when stimulus was absent. These findings suggest that S. siamkayai is more sensitive to insect-related odors and behaves as an active ambush forager. This high responsiveness appears to be a key behavioral trait for infecting insect pests that actively move near the soil surface in tropical regions.